2021
DOI: 10.1136/bmjopen-2021-052016
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of global human papillomavirus vaccination coverage: analysis of country-level indicators

Abstract: BackgroundMortality rates from cervical cancer demonstrate deep inequality in health between richer and poorer populations. Over 310 000 women died of this preventable disease in 2018, mostly in low-income and middle-income countries (LMICs) where screening and treatment are beyond the capacity of health systems. Immunisation against human papillomavirus (HPV) offers a primary prevention strategy, but rates of vaccination uptake are unclear. Understanding coverage levels and factors affecting uptake can inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 39 publications
1
44
1
1
Order By: Relevance
“…In a relatively low number of countries (76/195, 39%), the HPV vaccine has been introduced as mandatory and in most cases for young females, with a gradient of application ranging from 10% for low-income countries to 69% for high-income countries, thus clearly indicating the negative influence of poverty on the possibility of introducing this relatively expensive vaccine. The global HPV vaccination coverage is estimated to be as low as 12.2% [ 290 ]. Australia was the first country to organize, in 2007, an eradication program of the cancer of the cervix [ 291 ].…”
Section: Vaccine-preventable Infectious Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a relatively low number of countries (76/195, 39%), the HPV vaccine has been introduced as mandatory and in most cases for young females, with a gradient of application ranging from 10% for low-income countries to 69% for high-income countries, thus clearly indicating the negative influence of poverty on the possibility of introducing this relatively expensive vaccine. The global HPV vaccination coverage is estimated to be as low as 12.2% [ 290 ]. Australia was the first country to organize, in 2007, an eradication program of the cancer of the cervix [ 291 ].…”
Section: Vaccine-preventable Infectious Diseasesmentioning
confidence: 99%
“…Australia was the first country to organize, in 2007, an eradication program of the cancer of the cervix [ 291 ]. Despite that the fight against cervical cancer is a priority considering the high number of annual cases and deaths, especially in low-income countries [ 290 ], and for this reason, the vaccination campaign has mainly been addressed to young girls before starting sexual activity, the vaccination of the males should also be considered to prevent male cancers [ 292 ].…”
Section: Vaccine-preventable Infectious Diseasesmentioning
confidence: 99%
“…22,26,29 This will limit applicability to the global stage, especially to LMICs. 35 There was a range of methodological concerns in the included systematic reviews including small sample sizes, poor and/or incorrect reporting of statistical analyses in the primary studies and inappropriate combining of studies in meta-analyses. Importantly, the primary outcome across most studies was self-reported vaccination behaviour as opposed to actual vaccination behaviour and vaccination intent was often used as a proxy for vaccination receipt.…”
Section: Limitations Of the Evidence Basementioning
confidence: 99%
“…Bathalapalli has been conducting population-based screening programs, but it is not reaching all the population, as it is done opportunistically. In 2015, 59 million women worldwide received at least one vaccine, but only 1.4 million were from low income, and lower or middle income countries 4. If we want to change the history of cervical cancer, a true commitment is needed from all the national health programs, whatever the country, to extend the use of vaccines.…”
Section: Preventive Oncology Work In Rural Development Trust Hospitalsmentioning
confidence: 99%